Peran dan Tanggung Jawab Notaris Dalam Pelayanan Kepada Publik Sesuai Dengan Moral Etika Profesi dan Undang-Undang - Bondi, Adipapa Jefrianto; Aradoni, Emanuel Bryan; Naif, Maria Yovita; Rabawati, Dwityas Witarti (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The existence of a notary as a public official who has the authority to make authentic deeds has actually been confirmed in Article 1868 of the Civil Code. However, in reality, what happens sometimes is: authentic deeds which are ascertained by the notary not only are intervened by the government but also involve a lot of problems that lead to lawsuits in court, even though the notary has the role of authenticating the deeds that provide legal certainty (vide Article 1970 of the Civil Code) in private legal actions. Therefore, the problem is how the role and responsibility of the notary in service to the public can be in accordance with the profession’s ethical morals and laws. To answer the problem, the method used is critical legal studies. Both Article 1868 and Article 1870 of the Civil Code as well as the laws on the position of notaries are used as the analytic blades to the problem. Referring to such provisions, it is concluded that authentic deeds area perfect proofthat aimsto ensure legal certainty and protection, for the parties. Thus, order can be created in the traffic of private law. The role of a notary is seen from the legality and formalityof an authentic deed which must be met by those appearing, and those appearing arerecognized by the notary. In order for the role and responsibility to be carried out properly, a notary is demanded by the profession’sethical morals (code of ethics) and laws on notary position. Such responsibility is a logical consequence that must be requested from a legal profession including a notary in carrying out his or her duties. The responsibility is not only based on morals but also based on laws especially Law Number 30 of 2004 on Notary Position, in conjunction with Law Number 2 of 2014 on Notary Position